2018
DOI: 10.1186/s12884-018-2151-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal obesity on the success of assisted vaginal delivery in Chinese women

Abstract: BackgroundWe examined the influence of pre-pregnancy body weight on the rates of attempted and successfully assisted-vaginal delivery.MethodsWe used 2008–2016 inpatient records including 3408 women who had singleton gestations and needed operative delivery assistance to conduct a retrospective cohort study. Patients were categorized based on pre-pregnancy BMI (normal weight = 18.5 to less than 25 or obese = 30 or greater). We used logistic regression to estimate odds ratios and 95% confidence intervals of atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…From our cross-sectional study, the prevalence of OVDs was higher among women that were underweight, while obese patients had the highest prevalence of vaginal deliveries. We also found that the odds of OVDs reduces with increasing BMI as was also reported by Yu and Wue in China and other authors [ 43 , 44 ]. This finding may also suggest that patients with higher BMI may have very roomy pelvis and may not require assisted delivery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From our cross-sectional study, the prevalence of OVDs was higher among women that were underweight, while obese patients had the highest prevalence of vaginal deliveries. We also found that the odds of OVDs reduces with increasing BMI as was also reported by Yu and Wue in China and other authors [ 43 , 44 ]. This finding may also suggest that patients with higher BMI may have very roomy pelvis and may not require assisted delivery.…”
Section: Discussionsupporting
confidence: 90%
“…This observed reduced odds of OVDs with increasing BMI will only be valid among women with adequate pelvis, as one of the requirements for OVD is a clinically adjudged adequate pelvis with no feature of cephalopelvic disproportion [ 45 ]. However, this pattern may not be absolute as increased birthweight and increased prevalence of medical conditions in pregnancy such as hypertension, cardiac disease and diabetes may be commoner among obese women thereby leading to increased caesarean section rates among obese women [ 43 , 46 , 47 , 48 ]. Since one of the indications for OVDs is prolonged second stage of labor, it may not be surprising that there were 11% higher odds of OVDs for every extra hour of labor.…”
Section: Discussionmentioning
confidence: 99%
“…and, to some extent, this is driven by medical staff seeking to minimise risk to the baby and mother. Women who are obese and whose labour is not progressing are less likely than women of ideal weight to be allowed to attempt a vaginal delivery with assistance from forceps or a vacuum cap (ventouse), but, when they are allowed to do so, appear to have better outcomes than ideal weight women 88,89 . With caesarean section recovery is slower and surgical complications are more likely with obesity 90,91 …”
Section: Labour Complicationsmentioning
confidence: 99%
“…Women who are obese and whose labour is not progressing are less likely than women of ideal weight to be allowed to attempt a vaginal delivery with assistance from forceps or a vacuum cap (ventouse), but, when they are allowed to do so, appear to have better outcomes than ideal weight women. 88,89 With caesarean section recovery is slower and surgical complications are more likely with obesity. 90,91 Post-partum haemorrhage occurs in up to 5% of women and is characterised by either heavy blood loss during delivery (in excess of 500 ml following vaginal delivery or 1 litre following a caesarean) or in the following days (as a result of placental retention, uterine atony or rupture).…”
Section: Labour Complicationsmentioning
confidence: 99%
“…Many studies have identi ed women with high BMIs as an independent risk factor for vaginal delivery [35,36]. A cohort study, which included more than 5,000 parturients, found that compared to women with a BMI less than 30, obese women with a higher BMI had a longer duration and slower progression of the rst stage of labour, but no differences were found in the timing of cervical dilation from 6 cm to complete dilation [37].…”
Section: Discussionmentioning
confidence: 99%